The Influence Of Smartphone User Interface On Consumer Purchase Intention - Dika Chandrasa Yudha Prasetya; Etwin Hendri Irawan; Irfan Raihansyah Kusharmoyo; Dwi Hartanti (JMB : Jurnal Manajemen dan Bisnis, 2026)
One of the reasons why a smartphone product fails is due to a suboptimal user interface. A suboptimal user interface makes users hesitate to purchase the smartphone product. This study aims to determine the effect of the user interface on consumer purchasing interest. Several influencing factors include design, features, comfort, ease, and optimization of the user interface. This study uses a linear regression method. The sampling technique was conducted by distributing a Google form via WhatsApp, resulting in a sample size of 50 respondents. Using linear regression analysis, the relationship between the predictor variable x = 1 and the response variable y was 3.2585 with a regression equation of y = 2.798 + 0.4605x. The results of this study prove that smartphone UI influences consumer purchasing interest.Â Keyword:Â User Interface, Smartphone, Purchase Intention